Factors influencing urban households’ food needs in Minna Metropolis, Niger State, Nigeria - Uzoma; Kawu (Global Journal of Food and Agribusiness Management, 2024)
Spawn Rice, yam, and cowpea are examples of agricultural items that are important to urban inhabitants' diets. However, Nigerian urban food prices are still in danger due to rising agricultural production costs. The factors influencing urban families' demand for food commodities in Minna city were examined in this study. 110 heads of households in metropolitan areas who were chosen using a three-stage random sample method provided the data. The multiple regression technique was used to evaluate the data gathered for the investigation. The findings demonstrated the price inelasticity of cowpea, yam, and rice. Cowpea, yam, and rice had cross-price elasticities of 0.005, 0.028, and -0.132, respectively. The calculated income elasticity of demand, cross price, and own price for rice were 0.018, -0.132, and -0.308, respectively. The calculated values for yam were -1.262, 0.028, and 0.289, in that order. These values, however, were -0.530, 0.005, and 0.002 for cowpea, respectively. Yam was found to be a luxury product for income elasticity, while rice and cowpea were shown to be typical goods. To reduce the inflationary pressure on food products in metropolitan areas, the food aids program and other social protection measures should be implemented.